Executive functioning, behavioural, emotional, and cognitive difficulties in school-aged children prenatally exposed to methadone - Spowart, Katherine M.; Reilly, Kasey; Mactier, Helen; Hamilton, Ruth (Frontiers in Pediatrics, 2023)
Aim: The aim of this study was to examine executive function and emotional and behavioural difficulties of children aged between eight and 10 years who had been prenatally exposed to methadone, compared to non-exposed peers. Methods: Prospective study: third follow up of an original cohort of 155 children born to methadone-maintained opioid dependent mothers 2008–10: previous investigations were at 1–3 days and at 6–7 months of age. Carers completed the Strength and Difficulties Questionnaire (SDQ) and the Behaviour Rating Inventory of Executive Function; Second Edition. Results were compared between exposed and non-exposed groups. Results: Carers of 33 of 145 traceable children completed the measures. SDQ responses showed no group differences on subscales of emotional symptoms, conduct problems, or peer relationship problems. A marginally higher proportion of exposed children had a high or very high hyperactivity subscale score. Exposed children scored significantly higher on BRIEF®2 behavioural, emotional and cognitive regulation indices, and on the global executive composite. After controlling for potentially confounding higher reported maternal tobacco use in the exposed group via regression modelling, the effect of methadone exposure reduced. Interpretation: This study supports evidence that methadone exposure in utero is associated with adverse neurodevelopmental outcomes in childhood. Challenges in studying this population include difficulties with long-term follow-up and controlling for potentially confounding factors. Further investigation of the safety of methadone and other opioids in pregnancy must include consideration of maternal tobacco use.